Penggunaan Uji Mann-Whitney pada Analisis Pengaruh Pelatihan Wiraniaga dalam Penjualan Produk Baru - Sriwidadi, Teguh (Bina Nusantara University, 2011)
This research is conducted in PT Merapi Utama Pharma in order to determine the influence of training to the sales force in selling a new product. The methodology is Mann-Whitney Test manually using formula and table, and using Statistical Programs for Social Studies ( SPSS ). The research result that the average sales volume of the trained sales forces is the same as the average sales volume of the untrained sales force.Â